Review of the Helochares (Hydrobaticus) MacLeay of the New World (Coleoptera: Hydrophilidae: Acidocerinae) - Short, Andrew Edward Z.; Girón, Jennifer C. (Zootaxa, 2018)
New World species assigned to the Helochares subgenus Hydrobaticus MacLeay are reviewed based on adult morphology and DNA sequence data. Nine species are recognized, including five here described as new: Helochares (Hydrobaticus) laevis n. sp. (Mexico), H. (Hydrobaticus) nexus n. sp. (Ecuador, Panama, Venezuela), H. (Hydrobaticus) politus n. sp. (Guatemala), H. (Hydrobaticus) trujillo n. sp. (Venezuela), and H. (Hydrobaticus) zamora n. sp. (Ecuador). New records are provided for the three previously described species: Helochares (Hydrobaticus) championi Sharp, 1882 (Costa Rica, Guatemala, Nicaragua), H. (Hydrobaticus) maculicollis Mulsant, 1844 (United States), and H. (Hydrobaticus) normatus (LeConte, 1861) (United States to Costa Rica). A ninth species, known only from five poorly preserved female specimens from Peru, is left undescribed until additional material can be found. Most species are known to exhibit some parental care, with the egg case being attached to the abdomen of and carried by the female. Intraspecific genetic distances within several species are very high, in some cases more than 8% in the mitochondrial gene COI, suggesting there may be additional cryptic species remaining to be identified. All taxa are illustrated and a key to species is provided.